Identifikasi Waste pada Waktu Tunggu Pasien Rumah Sakit Nasional Diponegoro dengan Pendekatan Lean Hospital - Jessica Christanti Pualamsyah; Sudiro Sudiro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Outpatient waiting time based on minimum standart of care is defined as a time duration since patient in registrated until they meet the doctor. Lean management is a method that could improve outpatient process. There was persistence complain in outpatient waiting time in Diponegoro National Hospital since May 2016 until November 2016. Therefore, lean is expected to improve outpatient wait time. Based on Lean theory, waste is comprised of waste defect, overproduction, transportation, waiting, inventory, motion, overprocessing, and non-utilized talent. This study is going to identified waste that occurred in internal medicine outpatient. This was qualitative study research and conducted by observation, indepth interview, and focussed group disscusion. Total of key informant was 10 internal medicine patients and 6 hospital staffs, including registration, administration, information technology (IT) , procurement, helper, and nurse. Total of informant triangulation was 2 informants, including head of outpatient unit and medical records unit. Waste identification was done by value stream mapping analysis and value-added assessment. Root cause analysis (RCA) which used in this study was 5 whys method. The longest activity in outpatient was waiting in registration booth with mean value of 30,9 minutes, the second was waiting for doctor activity with mean value of 25,2 minutes and the third was waiting medical records to be given by helper with mean value of 8,8 minutes. Waste waiting, overprocessing, defect, inventory, motion were found in this study. It recommends an establisment of flowchart for patient, interdepartment coordination, and Standar Operation Procedure (SOP). Procrument for medical record facility and implementation of 6 S culture are mandatory.